2022
DOI: 10.1111/os.13424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Oral Electrolyte‐Carbohydrate Nutrition Supplement on Postoperative Outcomes in Elderly Patients Receiving Total Knee Arthroplasty: A Prospective Randomized Controlled Trial

Abstract: Objective Patients undergoing total knee arthroplasty (TKA) were primarily geriatric, with high risk of postoperative electrolyte disorders and malnutrition. Randomized controlled trials regarding oral nutrition supplement (ONS) strategies in TKA was sparse. This study aimed to evaluate the efficacy of preoperative oral electrolyte‐carbohydrate nutrition supplement (OECNS) on patients (aged >65 years) undergoing TKA. Methods From April 2019 to January 2020, 94 patients undergoing primary elective unilateral TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[1] As society ages, elderly orthopedic patients account for a considerable proportion of orthopedic patients, most of whom require surgical treatment, and the risk of electrolyte disorders and malnutrition after surgery is high. [2] Most organs in elderly people are already aging, and postoperative recovery is relatively slow, resulting in longer hospital stays. [1] In the perioperative care of elderly orthopedic patients, it is especially important to accelerate recovery, reduce pain of elderly patients, and reduce the incidence of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…[1] As society ages, elderly orthopedic patients account for a considerable proportion of orthopedic patients, most of whom require surgical treatment, and the risk of electrolyte disorders and malnutrition after surgery is high. [2] Most organs in elderly people are already aging, and postoperative recovery is relatively slow, resulting in longer hospital stays. [1] In the perioperative care of elderly orthopedic patients, it is especially important to accelerate recovery, reduce pain of elderly patients, and reduce the incidence of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is likely that, similarly to nonenterally fed patients, such patients experience the adverse effects of prolonged fasting: hunger, thirst, anxiety, increased pain. 7,8 Current guidelines do not provide preprocedural fasting recommendations for patients who receive tube feeding [9][10][11][12][13][14] and suggest an increased risk of pulmonary aspiration in this population. 14 The lack of clinical evidence or societal guidelines on optimal preprocedural fasting and an indication of increased risk in patients who receive tube feeding may promote unnecessary and potentially harmful restrictive fasting practices.…”
Section: Introductionmentioning
confidence: 99%
“…Data on harm from preoperative fasting in patients who are not critically ill who receive enteral feeding are scarce. However, it is likely that, similarly to nonenterally fed patients, such patients experience the adverse effects of prolonged fasting: hunger, thirst, anxiety, increased pain 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Of more significant concern is the high prevalence of malnutrition in the TJA population, ranging from 8.5% to 50%, suggesting that we have a considerable opportunity to improve their clinical outcomes further [ 18 ]. Recent studies have further confirmed that nutritional interventions for TJA patients could provide postoperative benefits [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%